Assessing Agroforestry Impact on Household Income: A Study of the Bu’u Bei Community Forest (HKm) in Tina Bani Village, Ende, Indonesia - Tiga, Elfrida Kastila Ine; Marimpan, Lusia Sulo; Mau, Astin Elise; Rammang, Nixon (Jurnal Wasian, 2024)
Agroforestry systems play a critical role in supporting livelihoods across East Nusa Tenggara, including in the Bu'u Bei Community Forest (HKm) in Tina Bani Village, Ende District, Ende Regency, Indonesia. This study investigates agroforestry patterns and evaluates their contribution to household income among the 47 HKm member households, surveyed through a census in April and May 2024. Employing both descriptive and quantitative analyses, our research reveals that the agrisilviculture system, characterised by a random mixed planting pattern, dominates agroforestry practices in the village. Path dependency, rooted in long-standing traditions, significantly shapes these practices. Agroforestry contributed significantly to household income in 2023, accounting for 98.87% of total income. However, poor infrastructure, particularly damaged roads, limits market access and reduces the economic potential of these systems. The study emphasises the need for integrated land management approaches that address infrastructure deficits while strengthening the resilience of agroforestry systems. This research provides critical insights into the socio-economic and environmental roles of agroforestry, offering a valuable reference for policymakers and stakeholders committed to promoting sustainable forest management and rural development in Indonesia.